Performance management and appraisal : in health services - Edis, Martin (London : Kogan Page, 1995)
This book is about Performance Management and Appraisal in Health Services.
Keywords: Great Britain; Performance standards; Health services; Performance standards -- Health services -- Great Britain; Personnel management -- Health services -- Great Britain; Health care teams -- Great Britain; Health services organisation and administration -- Great Britain